(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Puberty is the fundamental period for bone mass acquisition. In this period mineralization is found to increase with levels of high bone formation.. The objective of this cross-sectional study was to determine the changes in bone mineral density (BMD) and growth parameters for healthy pubertal males and females at different pubertal stages in Mosul city/Iraq. In addition, we aimed to detect the relationship between BMD, age, pubertal stage and growth parameters, and to reveal the most important determinant of BMD in the pubertal period. BMD of the lumbar spine was performed by dual-energy X-ray absorptiometry in (177) healthy pubertal children and adolescents (96 males, 81 females), aged (9.9-20.2) years. Growth parameters (Weight and height) were measured, BMI were calculated. Pubertal stages were assessed and the subjects were subdivided into 5 stages (Tanner stages of puberty for males and females). There was a significant effect of age and puberty on BMD. Females had significantly higher BMD across all age groups because females enter puberty earlier than males. When gender comparison was done according to pubertal stages, males had higher values for BMD in all pubertal stages , but without significant differences between them except in stage III, which indicated that boys gain more BMD than girls at this stage. Both sexes showed the main increments in BMD between stage IV and V. The major independent determinant of BMD in both sexes was pubertal stage. BMD of males was also highly correlated with growth parameters, but no such correlations for females. values in the study group were significantly lower than Western normative values, with Z scores for girls was (-1.2±1.2) and for boys was (-1.4±1.1). In conclusion, bone mass increased throughout puberty in both sexes and there was a strong evidence that pubertal development was consistent and independent predictors of BMD in healthy children and adolescents.